2019
DOI: 10.1186/s12917-019-1830-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and antimicrobial susceptibility profile of Escherichia coli isolated from backyard chicken in and around ambo, Central Ethiopia

Abstract: BackgroundEscherichia coli is bacteria that exist as commensal in the intestine of animals and humans, but pathogenic strains cause disease in chickens. The development of antimicrobial resistance in E. coli is one of major concern worldwide. A cross-sectional study was conducted from November, 2015 to April, 2016 in and around Ambo town on backyard chicken with the objectives of isolating E. coli from selected visceral organs, assessment of potential risk factor and determination of antimicrobial resistance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
23
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 16 publications
(17 reference statements)
10
23
4
Order By: Relevance
“…In this study, with the nutrient broth turbid, black centered colony with metallic sheen was observed in EMB agar. The present results similar to the findings of the Zinnah et al (2007) and Sarba et al (2019) presumptively recognized E. coli where they found in an EMB agar a greenish-black colony along with a metallic sheen. Same results were also found by some other authors (Buxton and Fraser, 1977;Freeman, 1985;Jones, 1987) whereas characteristic features of E. coli such as gram-negative, pink color, small rodshaped were noticed in gram's staining as well as hanging drop technique (Cowan, 1985) in which all the isolates showed motility.…”
Section: Resultssupporting
confidence: 92%
“…In this study, with the nutrient broth turbid, black centered colony with metallic sheen was observed in EMB agar. The present results similar to the findings of the Zinnah et al (2007) and Sarba et al (2019) presumptively recognized E. coli where they found in an EMB agar a greenish-black colony along with a metallic sheen. Same results were also found by some other authors (Buxton and Fraser, 1977;Freeman, 1985;Jones, 1987) whereas characteristic features of E. coli such as gram-negative, pink color, small rodshaped were noticed in gram's staining as well as hanging drop technique (Cowan, 1985) in which all the isolates showed motility.…”
Section: Resultssupporting
confidence: 92%
“…A recent study from Ethiopia has shown that the E. coli isolates were 100% susceptible to fluoroquinolones and sulfamethoxazole-trimethoprim, whereas the susceptibility to gentamicin, streptomycin, and kanamycin was 93%, 85%, and 75% respectively. 33 However, a few studies have reported highly resistant strains of E. coli which were resistant to 100 resistant to nalidixic acid while the resistance to kanamycin and streptomycin was 77% and 67% respectively. 34 These variations may be attributed to the differences in the use of antimicrobial agents in different regions in humans and poultry or due to the presence of diverse clones of E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, several earlier investigations in broiler chickens with colibacillosis reported 20% to 80% prevalence of this infectious disease [ 36 , 40 , 41 , 43 , 65 ]. The prevalence of colibacillosis in other countries like Nepal, China, Brazil, and India ranged from 30% to 80% [ 4 , 66 , 67 , 68 ]. The predisposing epidemiologic factors such as geographic locations, farm housing types, varying sample collection, transportation and preservation methods, and management practices are likely to contribute to the differences in frequency of pathogenic APEC isolation [ 67 ].…”
Section: Discussionmentioning
confidence: 99%